Gastrointestinal bezoars in paediatrics: Case series and literature review - Mohamed Ahmed Elghazeery; Alhassan Mohamed Hassan (Wolters Kluwer Medknow Publications, 2024)
Background: Bezoars are indigestible lumps which are usually found in stomach. Types of bezoar include phytobezoar, trichobezoar, lithobezoar, pharmacobezoar, plasticobezoar, lactobezoar and metal bezoar. Trichobezoars mostly affect females in 20s and 30s with a rarity in paediatrics. Unexplained complaints with a palpable mass are commonly found in these patients. Treatment involves retrieval of mass with searching for others. The purpose of this study was to present data and surgical management of cases with trichobezoars. Materials and Methods: We documented a retrospective review of trichobezoars done in our hospital between 2016 and 2022. All demographic data collected included gender and age of cases, composition and extent of bezoar, clinical presentation, imaging modalities, endoscopic trial, surgical approach and outcome. Results: Five cases of gastrointestinal tract (GIT) trichobezoars underwent surgery. All cases were females between (13 and 16 years). Trichobezoars were three gastric, one ileal and one of combined gastric and colonic. Complaints were abdominal pain, vomiting, weight loss and halitosis. Three cases had a palpable abdominal mass. Different radiological modalities were performed. Endoscopic retrieval was tried in one patient and the laparoscopic approach in another one, but the first route failed. Laparotomy followed by gastrotomy, enterotomy and colotomy was done without complications. Conclusions: Trichobezoars should be suspected in any child with unexplained abdominal complaints or with a palpable abdominal mass, especially in girls. Imaging can be done in different modalities for diagnosis. Endoscopic retrieval could be tried; however, its failure is common, necessitating laparotomy, which has an excellent outcome.